MELURUSKAN SEJARAH TRENGGALEK KOTA GAPLEK: STUDI HEURISTIK FOKLOR PANEMBAHAN BATORO KATONG, JOKO LENGKORO DAN MENAK SOPAL - Teguh Budiharso (Center of Language and Cultural Studies, 2015)
This study is aimed at describing toponymy of Trenggalek emphasizing on identification of local foklor about Batoro Katong, Joko Lengkoro and Menak Sopal. This study uses qualitative approach assigning heuristic and phenomenology as the method of inquiry. Primary sources such as documents on the foklor, babad, inscriptions, and sites of history were analyzed. Indepth analyses pertaining to the exploration using indepth interview and discussion were conducted involving various informants. This study reveals that Trenggalek derived from Galek, identifying a city that produced gaplek. Since early Matarm, gaplek had been produced in Trenggalek. In support to the name, Galek has been interpreted as the identity of “terang” and “galih” aspiring that Galek has received greatness of the King in Demak. Trenggalek did not exist in the era of Mataram, Majapahit, Demak, and Pajang Kingdom as a regency, however, its status as sima parashima, received since King Sindok in 929 AD up to Majapahit ruling indicated that Trenggalek was a prominent area. To some extents, Trenggalek has received discrimination in the government administration but the history remains to promote the legacy of Trenggalek as an autonomy regency.